El Niño‐Related Vertical Mixing Enhancement Under the Winter Mixed Layer at Western Subarctic North Pacific Station K2. Issue 11 (1st November 2021) - Nagano, Akira; Wakita, Masahide; Fujiki, Tetsuichi; Uchida, Hiroshi
Abstract: We conducted a current velocity and hydrographic time series observation in the upper ocean by deploying a mooring buoy at station K2 ( 47 ° N, 160 ° E) from July 2015 to June 2019 to understand the physical conditions that affect the acidification of the winter mixed layer (ML) water in the western subarctic North Pacific. Disturbances with substantial current velocity shear were excited by the wind changes remotely related to the 2015/2016 and 2018/2019 El Niño events. The density stratification beneath the ML was also weakened in winter, particularly the El Niño years. Based on the bulk Richardson number mixing scheme, we found that the El Niño‐related strengthening of the current velocity shear enhanced the vertical diffusivity beneath the winter ML driven by the near‐inertial current velocity variation. The weakening of the density stratification is ineffective in enhancing the vertical diffusivity. It is suggested that the El Niño‐related large vertical mixing accelerates the acidification of the winter ML water through the enhancement of the entrainment of the deep water that is rich in dissolved inorganic carbon. Plain Language Summary: The acidification of the sea's surface water in the western subarctic North Pacific is slower than the global mean ocean acidification. We observed the current velocity, temperature, and salinity in the upper ocean by deploying a mooring buoy at station K2 (47°N, 160°E) in the western subarctic North Pacific from July 2015 to June 2019 to understand which physical conditions affect the acidification. The current velocity varied noticeably, rotating clockwise near the frequency derived from the Earth's rotation, called the inertial frequency. Moreover, under the remote influence of the very warm sea surface condition in the central and eastern equatorial Pacific, namely El Niño, the vertical differences in the current velocity and the water density became large and small, respectively. The influences of El Niño were found to provide a favorable condition for the occurrences of strong vertical mixing beneath the winter mixed layer due to the near‐inertial current velocity variation. Based on the vertical mixing coefficient, we indicated the acceleration of the acidification due to the strengthening of the upward flux of dissolved inorganic carbon by occurrences of El Niño events. Key Points: Time series of current velocity and water density were obtained at K2 in the western subarctic North Pacific Shear‐driven vertical mixing is strengthened by the El Niño‐related current velocity change El Niño enhances upward dissolved inorganic carbon flux beneath the winter mixed layer and accelerates the acidification